2001
DOI: 10.1054/jhsb.2001.0679
|View full text |Cite
|
Sign up to set email alerts
|

Finger Sucking Digital Deformities

Abstract: We report our experience with severe digital deformities caused by prolonged finger sucking. Our analysis of nine patients demonstrated that the deformity was mainly located in the proximal and middle phalanges of the affected digit(s). We have reviewed the literature, enumerated the common patterns of "finger sucking" and explained the resulting deformities. Corrective osteotomy, preferably at the metacarpal base level, is required in severe deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…1). 2 The degree of rotational correction that can be achieved at the metacarpal level varies between fingers and is due to the tethering of the deep transverse metacarpal ligament. A cadaveric study has shown that corrections of up to 19°can be achieved in the index, middle, and ring fingers.…”
mentioning
confidence: 99%
“…1). 2 The degree of rotational correction that can be achieved at the metacarpal level varies between fingers and is due to the tethering of the deep transverse metacarpal ligament. A cadaveric study has shown that corrections of up to 19°can be achieved in the index, middle, and ring fingers.…”
mentioning
confidence: 99%
“…9 Esta técnica ha demostrado buenos resultados en secuelas rotacionales de las falanges media y proximal en pacientes adultos y pediátricos. 10 11 La ventaja en la utilización de los metacarpianos para la corrección de la deformidad radica en ser técnicamente mas sencilla, con menor disección y manipulación tendinosa, menor numero de adherencias, menor tendencia al retraso de consolidación y que la rotación en la articulación metacarpofalángica no genera una alteración en el buen resultado funcional. 12…”
Section: Discusionunclassified
“…Treatment of thumb-sucking habit using a fixed tongue crib appliance -a case report and literature review If the habit continues beyond the age of four to five years it is associated with dental changes in the primary, mixed and secondary dentition, such as an anterior open bite, 8 which frequently leads to a secondary tongue thrust habit. 14 Other changes include: Class II molar and canine relationship, 15 excessive overjet, 16,17 maxillary protrusion, 18 posterior cross bite, 19 digital deformity 20 and paronychia. 21 The adverse effects associated with thumb sucking are dependent on its frequency, intensity, duration and position of the digit in the mouth.…”
Section: Introduction Aetiologymentioning
confidence: 99%